Pengaruh Kualitas Produk, Persepsi Harga dan Suasana Terhadap Kepuasan Pelanggan di Ambiente Ristorante - Linda Nurmalita; Hariadi Hadisuwarno (BULLET : Jurnal Multidisiplin Ilmu, 2023)
In every culinary business or culinary business, customer satification is very importany to running a bussines also effect profitability, especially Ambiente Ristorante. This study aims to analyze the effect of produt quality (X1), price perception (X2), atmosphere (X3) as independent variables of customer satisfaction (Y) at Ambiente Ristorante. This study uses a quantitative design with survey methods and purposive sampling. Participants consisted of (n-100) individuals who had visited Ambiente Ristorante. The data collected from the respondents in the distributed survey were subjected to multiple regression analysis fot the purpose of analysis. Primary data obtained directly from the respondents. Based on the result of the study, Product Quality (X1), Perceived Price (X2), also Atmosphere (X3) have a sifnificant impact of Customer Satisfaction (Y) partially or simultaneously at Ambiente Ristorante. In summary, it can be concluded that Product Quality (X1), Perceived Price (X2), Atmosphere (X3) play a very important role in customer satisfaction to continue visiting Ambiente Ristorante.